Effect of environmental condition on essential work of fracture of proton exchange membranes - Thibaud VERMOT DES ROCHES (The Japan Society of Mechanical Engineers, 2015)
The essential work of fracture (EWF) is a key property in understanding the fracture resistance in polymer membranes. As such, it is a promising approach when investigating the fracture resistance of proton exchange membrane in fuel cells. The longevity of these membranes is crucial to the good function of the cell: the membranes have to sustain important variations in the surrounding temperature and humidity, possibly affecting their fracture resistance. This study investigated the essential work of fracture of such proton exchange membranes using a double-edge notch tensile test (DENT test). The tests were performed for different environmental conditions that were relevant to the conditions met by proton exchange membrane fuel cells. The results of the DENT tests strongly depend on the temperature and humidity; in particular the high temperature cases show a large increase of dissipated energy. Based on experimental results, a numerical model was developed and the numerical simulations of DENT tests were performed. The obtained results suggest that the shape factor of plastic zone, β, should be a function of the ligament length and the quadratic regression is appropriate to the calculation of EWFs when the temperature is near the glass transition temperature. The EWFs under ambient temperature (30 °C) conditions were found to be 18.4 kJ/m2 for 50 %RH and 21.5 kJ/m2 for 100 %RH. Those under high temperature (80 °C) conditions were found to be 48.0 kJ/m2 for 50 %RH and 56.4 kJ/m2 for 100 %RH.